Unicompartmental knee replacement for patients with partial thickness cartilage loss in the affected compartment. - Pandit, H; Gulati, A; Jenkins, C; Barker, K; Price, A; Dodd, C; Murray, D (2011)
It is recommended that in medial compartment osteoarthritis (OA) unicompartmental knee replacement (UKR) should not be undertaken unless there is bone on bone. This recommendation is not evidence based and it is important to know if it is correct as there are many patients with pain and partial thickness cartilage loss (PTCL) who could potentially benefit from UKR. The aim of this study was to determine if the recommendation is valid. From our database of over 1000 patients treated with the Oxford UKR, we identified 29 with medial OA that had PTCL, confirmed at operation, but otherwise satisfied the recommended indications. This group was matched with 29 knees that had bone exposed (BE) on both sides of the medial compartment and 29 knees that had bone loss (BL) on both sides of the medial compartment. There was no significant difference in the demographics or preoperative scores between the three groups. At a mean follow up of 2 years (range 1-6) the Oxford Knee Score (OKS) of the PTCL group (mean 36 SD 10) was significantly (p < 0.001) worse than the OKS of either the bone exposed group (mean 43 SD 4) or the bone loss group (mean 43 SD 5). 21% of those with PTCL did not benefit substantially from the operation (increase in OKS ≤ 6), whereas all patients in the other groups did. We conclude that the results of UKR for PTCL are unpredictable and therefore that UKR should only be done for medial compartment OA if there is bone on bone. There is a need to develop a method to identify which patients with PTCL will do well so that this subgroup could be treated with UKR.